THE IMPACT OF INSTITUTIONAL OWNERSHIP AND MANAGERIAL OWNERSHIP ON LOAN LOSS PROVISION - Ardiany, Yuli; Lukviarman, Niki; Hamidi, Masyuri; Luthan, Elvira (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2022)
The objective of this study is to ascertain the impact that managerial and institutional ownership have on provisions for loan losses. For the period 2018-2022, the data utilized in this study comprises all banking companies that are publicly traded on the Indonesia Stock Exchange. Even though the banking industry has stricter regulations compared to other industries, earnings management is an action that is often carried out by company managers aimed at the manager's personal interests and the interests of the company.The research data underwent analysis using Eviews. The findings of the study indicated that managerial ownership did not have a statistically significant impact on loan loss provisions, while institutional ownership did have a significant negative effect. Institutional investors have been demonstrated to be effective monitoring proxies in the implementation of company policies; therefore, the findings of this study may serve as a benchmark when contemplating banking company policymaking, specifically in the investor selection process.Keyword : Asia, Bank, Institutional Ownership, Managerial Ownership, Loan Loss Provisions.